Effects of intranasal oxytocin on emotional face processing in women - Domes, Gregor; Lischke, Alexander; Berger, Christoph; Grossmann, Annette; Hauenstein, Karlheinz; Heinrichs, Markus; Herpertz, Sabine (Psychoneuroendocrinology, 2010)
The neuropeptide oxytocin (OXT) has previously been found to reduce amygdala reactivity to social and emotional stimuli in healthy men. The present study aimed to investigate the effect of intranasally administered OXT on brain activity in response to social emotional stimuli of varying valence in women. In a functional magnetic-resonance imaging study, sixteen women were presented with fearful, angry, happy and neutral facial expressions after a single dose of 24IU OXT or a placebo administration in a within-subject design. Group analysis revealed that the blood-oxygen-level-dependent (BOLD) signal was enhanced in the left amygdala, the fusiform gyrus and the superior temporal gyrus in response to fearful faces and in the inferior frontal gyrus in response to angry and happy faces following OXT treatment. This effect was independent of fixation pattern to specific sections of the facial stimuli as revealed by eye tracking and independent of basal plasma levels of OXT, estradiol, and progesterone. The results are at odds with the previously reported effects found in men. Future studies should include both sexes to determine a possible sexual dimorphism in the neural effects of OXT, considering gonadal steroids and OXT receptor affinity.